2015
DOI: 10.1248/cpb.c15-00400
|View full text |Cite
|
Sign up to set email alerts
|

Schisandrosides A–D, Dibenzocyclooctadiene Lignan Glucosides from the Roots of <i>Schisandra chinensis</i>

Abstract: Four new dibenzocyclooctadiene lignan glucosides, schisandrosides A-D (1-4), as well as two known rare nortriterpenoids, micrandilactone C (5) and propindilactone Q (6), were isolated from the roots of Schisandra chinensis BAILLON (Schisandraceae). The structure of compounds 1-4 were elucidated by physical and spectroscopic data interpretation. To the best of our knowledge, schisandrosides A-D (1-4) represent the first example of a dibenzocyclooctadiene lignan glycoside.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…Chemical structures of the isolated compounds were determined by NMR. All structures were consistent with previously published data [ 28 ]. Gomisin B (95%) and gomisin C (98%) were purchased from Toronto Research Chemical (Toronto, ON, Canada) and Sigma-Aldrich, respectively.…”
Section: Methodssupporting
confidence: 91%
“…Chemical structures of the isolated compounds were determined by NMR. All structures were consistent with previously published data [ 28 ]. Gomisin B (95%) and gomisin C (98%) were purchased from Toronto Research Chemical (Toronto, ON, Canada) and Sigma-Aldrich, respectively.…”
Section: Methodssupporting
confidence: 91%
“…Combined with DEPT‐135, HSQC and 13 C‐NMR data, compound 1 exhibited signals for 32 carbons, including 12 aromatic carbons ( δ C 153.2, 152.6, 151.2, 143.3, 141.9, 140.7, 136.3, 136.2, 125.4, 124.3, 114.2, 116.6), four methoxy groups ( δ C 61.9, 61.3, 61.1, 56.6), two methyl groups ( δ C 29.6, 16.4), one oxymethine signals ( δ C 73.8), a glucose group ( δ C 102.6, 78.0, 78.0, 75.1, 71.4, 62.5), as well as an angeloyl group ( δ C 167.0, 139.5, 128.7, 20.7, 15.8; Table ), indicating that compound 1 belonged to the C 18 ‐dibenzocyclooctadiene lignan with a glucose moiety and an angeloyl group. Compared the 1D NMR data of compound 1 with literatures, it was found that compound 1 was similar to schisandroside B ( 7 ) . The obvious difference between them was that a methoxy group in schisandroside B was substituted by an angeloyl group at C‐12 in 1 .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, thirteen known compounds 3 – 15 were identified as gomisin F ( 3 ), (−)‐tigloyldeangeloylgomisin F ( 4 ), angeloylgomisin Q ( 5 ), schisandrin ( 6 ), schisandroside B ( 7 ), schisandroside A ( 8 ), pregomisin ( 9 ), 8,8′‐dihydroxypinoresinol ( 10 ), 8‐hydroxypinoresinol ( 11 ), ( R )‐ p ‐cymene 9‐ O ‐ α ‐ d ‐arabinofuranosyl‐(1→6)‐ β ‐ d ‐glucopyranoside ( 12 ), 15‐hydroxy‐ α ‐cadinol ( 13 ), guaidiol ( 14 ), 3 β ‐hydroxy‐5 α ,6 α ‐epoxy‐ β ‐ionone ( 15 ), by comparing the NMR data with the published data in the literatures. Compounds 13 – 15 were isolated firstly from Schisandraceae, and they might provide some new insights to biosynthetic pathway of other compounds, such as triterpenoids or schinortriterpenoids.…”
Section: Resultsmentioning
confidence: 99%
“…[1] Until now, there are little research were conducted on the chemical compounds of the roots of S. chinensis, which led to isolated lignans and triterpenoids from the roots, while pharmacology studies were displayed that this plant has anti-inflammatory, anti-tumor activities, and so on. [2][3][4] In summary, the roots of S. chinensis have extremely high research value. Therefore, in this study, we have separated one new phenylpropanoid schineolignin D (1), one new sesquiterpene (À )-(7S,10S)-3,11,12,13-tetrahydroxycalamenene (2), one new quinic acid 4-(E)-O-coumaroylquinic acid ethyl ester (3), and seven known compounds (4 -10) from the roots of S. chinensis (Figure 1).…”
Section: Introductionmentioning
confidence: 98%
“…To promote further studies on the plant, many phytochemistry and pharmacology studies focus on the different parts of S. chinensis [1] . Until now, there are little research were conducted on the chemical compounds of the roots of S. chinensis , which led to isolated lignans and triterpenoids from the roots, while pharmacology studies were displayed that this plant has anti‐inflammatory, anti‐tumor activities, and so on [2–4] …”
Section: Introductionmentioning
confidence: 99%